Visual Impairment, Partially Dependent ADL and Extremely Old Age Could be Predictors for Severe Fall Injuries in Acute Care Settings - Hidetoshi Aihara; Masaki Tago; Toru Oishi; Naoko E. Katsuki; Shu-ichi Yamashita (International Journal of Gerontology, 2018)
Summary: Background: Severe fall injuries in inpatients extend hospital stay, increase medical costs, and shorten patients' healthy life expectancy. The objective of this study was to clarify the predictors for severe fall injuries requiring treatments of inpatients in acute care settings. Methods: We retrospectively analysed adult inpatients who suffered falls in an acute care hospital in Kyushu, Japan from April 2012 to January 2015. Using hospital record data, we compared patients who had required treatments after falls with those who had not by univariate and multivariate analyses. Results: Among 371 patients who suffered falls, the median age was 83 years (interquartile range: 78–87 years). Fall required treatments in 46 patients (12%). In those required treatments, univariate analysis revealed higher percentages of patients with visual impairment (OR: 4.1, 95%CI: 1.3–12.8, p = 0.023) and a bedriddenness rank of A (partial dependence with housebound status) (OR: 2.4, 95%CI: 1.3–4.5, p = 0.006) as well as patients aged ≥85 years (OR: 1.9, 95%CI: 1.0–3.6, p = 0.039). There were lower percentages of patients with a cognitive function score of 4 (requiring constant assistance with symptoms interfering with daily activities) (p = 0.008). In multivariate analysis, age of ≥85 years (OR: 2.2, 95%CI: 1.1–4.2, p = 0.021), visual impairment (OR: 4.2, 95%CI: 1.3–13.9, p = 0.019), and a bedriddenness rank of A (OR: 2.4, 95%CI: 1.3–4.7, p = 0.009) were associated with falls requiring treatment. Conclusion: Visual impairment, partial dependence in activities of daily living and 85 years of age or older could be useful predictors for severe fall injuries. Keywords: bedriddenness rank, cognitive function score, severe fall injuries, severity of incidents and accidents